Numerical study of flow reversal during bubble growth and confinement of flow boiling in microchannels. (October 2021) - Lin, Yuhao; Luo, Yang; Li, Wei; Li, Junye; Sun, Zhichuan; Cao, Yanlong; Minkowycz, W.J.
Highlights: Bubble growth and confinement in one of the two nearby microchannels is investigated numerically. The flow reversal caused by bubble elongation and flow maldistribution is discussed. Finned microchannel can suppress the flow reversal and enhance the heat transfer performance. Abstract: The flow boiling instability caused by confined bubbles generated during the flow boiling process in parallel microchannels leads to flow reversal and earlier critical heat flux (CHF), which is a major problem with the extensive application of two-phase flow in microchannel heat sinks. In this study, single bubble growth in one of the two nearby microchannels is investigated through numerical methods. The VOF method, Hardt's phase-change model, conjugate heat transfer between solid and fluid domains were adopted within a self-developed OpenFOAM solver. After the growing bubble being confined by the sidewalls, the flow path of the channel is blocked thus the inlet liquid flow tends to flow into the other channels instead of pushing the confined bubble, which caused the confined bubble to extend towards upstream and flow reversal. By increasing the mass flux, the flow reversal is suppressed, but the flow boiling heat transfer enhancement is minimized due to the less evaporation area. The method of combination of microchannel and microgap (CMC) has little effect on flow reversal until the bubble enters the microgap. And its thermal performance is worse than the original heat sink. The confined bubble in the finned microchannel (FMC) heat sink would flow into the nearby channel through the secondary channel between the fins thus prevent flow reversal. Furthermore, the evaporation area between the bubble and solid walls increases, thus significantly lower thermal resistance (for about 40%) can be obtained. Considering the overall flow stability and heat transfer performance, the finned microchannel is recommended to be fabricated in industrial applications.